Effect of cutting speed and feed per tooth on the trimmed surface roughness and tool wear during milling of CFRP : Aerostructural part - Sundi @ Suandi, Syahrul Azwan; Abdul Hakim, Izzat Afandi; Mahadi, Mohd Farid; Nazar Shah, Noramin; Raja Abdullah, Raja Izamshah; Othman, Intan Sharhida; Kasim, Mohd Shahir; Noordin, Mohd Nor Hafizi (Universiti Putra Malaysia Press, 2024)
The machining quality plays a pivotal role in determining the service life of components. In this context, the primary focus of the experimental investigation is centered on the impact of cutting conditions during edge trimming of carbon fiber reinforced plastics (CFRP) material. The ultimate objective of this experiment is to pinpoint the most effective machining parameters, specifically the cutting speed, Vᶜ and the feed per tooth, fᶻ, to minimize damages during the edge trimming process using actual aerostructural sample components composed of CFRP material. Furthermore, the study took into account the issue of tool wear on cutting tools. The Design of Experiment (DoE) technique, specifically the Taguchi L₉ orthogonal arrays method, was used to conduct this research. It was shown that the feed per tooth, fᶻ, and the cutting speed, Vᶜ, had the biggest effects on the trimmed surface quality as the longitudinal surface roughness increased. It was demonstrated that the fracture of the pyramidal tooltips in router-type tools happened more frequently at higher cutting speeds, Vᶜ. The optimal machining parameters for minimizing damages during CFRP edge trimming were the combination of the feed per tooth, fᶻ at 0.05 mm and cutting speed, Vᶜ at 50 m/min. The most significant element influencing the tool’s wear was the cutting speed, Vᶜ.